Tashbih baligh in the last thirty parts of the Qur'an: A study of the eloquent styles and vocabulary and their artistic impact - Fudhaili, Achmad (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The thirtieth part of the Quran is distinguished by its eloquent language and refined artistic style. This part contains a collection of short surahs characterized by high rhetorical density and heavily relies on the use of eloquent similes as a rhetorical device to convey meanings in an impactful and captivating manner. Considering that it represents one of the highest forms of simile in the Arabic language, this study aims to analyze these eloquent similes and understand their role in highlighting the rhetorical and aesthetic meanings in the Quranic text. This research adopts a qualitative analytical methodology based on the study of Quranic texts and their interpretations. The researcher collected data from the Quranic text and analyzed it by gathering the Quranic verses, identifying them, classifying them, analyzing them, interpreting their meanings, discussing them, and drawing conclusions. The results of this research show that the number of similes in the thirtieth part is 21 eloquent similes, divided into three main forms: 19 similes in the form of the subject and predicate or similar structures, one simile in the form of addition, and one simile in the form of the state and its owner. These eloquent similes are characterized by the brevity of their words and the omission of their components due to the strength and beauty of expression. Consequently, this research concludes that the use of eloquent similes in the Quran significantly enhances the deeper meaning of the Quranic verses and brings out their beauty, making them more enjoyable and attractive to people.